HUBUNGAN MOTIVASI KERJA PEGAWAI DENGAN PRODUKTIVITAS KERJA PEGAWAI KANTOR CAMAT TIGABINANGA KABUPATEN KARO - Novalina Kartika Sari Br Karo; Marlon Sihombing; Simson Ginting (Jurnal Darma Agung, 2021)
The theory used in the motivation variable is Herzberg's Motivation Theory in which motivation is divided into two, namely intrinsic and extrinsic motivation, then Maslow's Hierarchy of Needs Theory. One of the data collection techniques used in this research is through questionnaires and literature review of the object under study. From the results of hypothesis testing with a simple correlation (bivariate) that has been done, it shows that: There is a strong and real positive relationship between Employee Work Motivation (X) and Work Productivity (Y). This shows that the higher the level of work motivation, the better the performance will be. The partial correlation hypothesis testing shows that: There is a positive and real relationship between Work Motivation (X) and Work Productivity (Y), which indicates that the higher the level of Work Motivation, the better the productivity. The correlation value between X and Y is 0.714, indicating that there is a close relationship between Work Motivation and Work Productivity. Hypothesis testing to see the relationship between the level of motivation and productivity is tested simultaneously. The test results show that there is a close and real relationship between the level of work motivation and work productivity, which is equal to 0.714